2020
DOI: 10.5005/jp-journals-10071-23660
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Intensive Care Unit Admissions during COVID-19 Pandemic—A Single Center Experience

Abstract: A bstract Aim The impact of coronavirus disease 2019 (COVID-19) lockdown on cardiac emergency admissions to hospitals has been reported previously. We aimed to study the emergency room (ER) admissions to cardiac intensive care unit (CICU) at a tertiary care center during that period and compare this with admissions during the same time frame in the previous years. Materials and methods This is a retrospective observational study of patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…s e e m a n u s c r i p t D O I f o r d e t a i l s has also revealed that myocardial infarction or cardiovascular injury among patients suffering from COVID-19 increases the chances of death [5]. A recent observational study conducted at global levels has shown high coagulation and thrombotic events rates among COVID-19 patients admitted in Intensive care units [6].The consequences of heart failure and other inflammation-type responses, despite not having any prior history, have also been observed in several types of research [7]. Several studies have also indicated that the suffering of SARS CoV-2 actually doubled due to the presence of cardiovascular complications, which made life more difficult and mortality more prevalent [8].…”
Section: W I T H D R a W Nmentioning
confidence: 99%
“…s e e m a n u s c r i p t D O I f o r d e t a i l s has also revealed that myocardial infarction or cardiovascular injury among patients suffering from COVID-19 increases the chances of death [5]. A recent observational study conducted at global levels has shown high coagulation and thrombotic events rates among COVID-19 patients admitted in Intensive care units [6].The consequences of heart failure and other inflammation-type responses, despite not having any prior history, have also been observed in several types of research [7]. Several studies have also indicated that the suffering of SARS CoV-2 actually doubled due to the presence of cardiovascular complications, which made life more difficult and mortality more prevalent [8].…”
Section: W I T H D R a W Nmentioning
confidence: 99%
“…The perceived decrease in non-COVID patients, notably in outpatient and elective surgeries followed by emergency procedures widely reported by study respondents mirrors the literature from the SARS pandemic and the MERS outbreak. 19 21 …”
Section: Discussionmentioning
confidence: 99%